(untitled) (Journal of Human Sciences, 2025)
The scenic image is one of the types of artistic image, and in poetry it is distinguished by its narrative dimensions within the text. It appears in the poetic text, establishes the narrative framework within it, and draws narrative elements that appear in the form of place, time, character, and event, and the scenic image is represented in a new form in which it is seen. The .text has left the ordinary and jumped to find a foothold within the boundaries of the visual arts (cinema and plastic art) in an attempt to monitor that identification between the different arts Which reveals the openness of the poetic text to it, especially our poet "Muhammad Al-Shaltami “", who employed it in clear craftsmanship, drawing brilliant pictorial paintings with it that abolished the demarcation of the boundaries between poetry and prose, and bridged the gap between verse and prose, and the importance of the study lies in revealing many of the realistic incidents that the poet went through and employed them. To embody his conceptual scene, the study aims to trace the scenic depiction in his poetry Which came at different levels, the most prominent of which was the descriptive level, which had many conceptual scenes, the most present of which was the description armed with audio, visual, and olfactory effects, which established the poetic scene, with the aim of creating an integrated scenic image (sound, color, movement), and despite the abundance of the poet’s production in This color, but I have not come across previous studies that dealt with the scenic image of our poet. As for the research hypotheses, the study will answer two questions: The first: What are the foundations of narrative scene photography in Al-Shaltami’s poetry, and the second: How did the poet employ the compelling circumstances that he went through in producing his poetic texts in their various forms until they became a path to scene embodiment, and the research aims to use the descriptive and analytical method to draw the features of the scene in the work of our poet, and this necessitated dividing the research into Introduction, three sections, and a conclusion, which organizes the three levels of scene photography (descriptive photography, dialogue photography, and narrative photography)